Herbicide Spray Penetration into Corn and Soybean Canopies Using Air-Induction Nozzles and a Drift Control Adjuvant. (7th November 2017) - Creech, Cody F.; Henry, Ryan S.; Hewitt, Andrew J.; Kruger, Greg R.
Abstract: Drift reduction technologies aim to eliminate the smaller droplets that occur with some sprays because these small droplets can move off-target in the wind. Commonly used drift reduction technologies such as air-induction nozzles and spray additives impact on reducing off-target movement is well documented, however, the impact on herbicide penetration into an established crop canopy is not well known. This experiment evaluated the canopy penetration and efficacy of glyphosate treatments applied using four nozzle types (XR11005, AIXR11005, AITTJ11005, and TTI11005), two carrier volume rates (94 and 187 L ha -1 ), and glyphosate applications with and without a commercial drift reducing adjuvant. Applications were made to corn and soybean fields using glyphosate applied at 1.26 kg ae ha -1 with liquid ammonium sulfate at 5% v/v. A rhodamine dye was added (0.025% v/v) to the spray tank of each mixture as a tracer. Mylar TM cards were placed in the field above the canopy, in the middle canopy, and on the ground for corn and above and below canopy for soybean. Five cards were at each position in the canopy arranged across the crop row. The addition of a drift reducing adjuvant did not impact canopy penetration. Doubling the carrier volume increased the amount of penetration proportionally and as such the percent reduction was not different. The TTI11005 nozzle had the greatest amount of spray penetration (28%) in the soybean canopies and the XR nozzle had the greatest amount (50%) in the corn canopies. Deposition across the row, beginning in-between the row crop and ending in the row of the crop was 44, 18, and 8% for soybean and 59, 50, and 36% for corn. For both crops, more than half of the herbicide application was captured in the crop canopy. Proper nozzle selection for canopy type can increase herbicide penetration and increasing the carrier volume will increase penetration proportionally.